Implemetasi Terapi Komplementer Akupresure Pada Ibu Hamil di Posyandu Matahari - Nelly Nugrawati; Nur Ekawati nur; Ayu Wijaya ayu; Andi Muhammad Adam Adam; Juneth Kasandra Angel Rikumahu Kasandra (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2023)
Complementary Therapy is a type of therapy that utilizes the field of health sciences which studies how to treat various diseases using traditional techniques. This therapy does not use commercial drugs, but uses various types of traditional medicine and therapy. Midwifery services, both conventional and complementary, must be carried out with due observance of service quality which is oriented towards the application of a code of ethics and service standards and satisfaction which refers to the application of the minimum requirements for midwifery services. One of the reasons complementary midwifery care is currently widely used is the desire to avoid the side effects of drugs. This community service was carried out at the Matahari posyandu in May 2023. The participants in this community service activity were pregnant women. The activity carried out was to train pregnant women to do acupressure independently. Complementary services need to get support from various health practitioners so that knowledge in complementary care develops